Detecting optical transients and variables with MeerLICHT - Paterson, Kerry (Department of Astronomy, 2019)
For a long time, the discovery of a transient in a one wavelength triggered observations in other wavelengths. Due to various constraints such as telescope access, scheduling and availability, and the need for human intervention, follow up observations of the transient event could take place long after the initial discovery. Due to the time-critical nature of some transients, with prompt emission that can fade rapidly, this delay in follow up observations can result in important information about the event being missed. Thus, the concept of MeerLICHT was born. MeerLICHT is an fully robotic, optical telescope whose main goal is the detection of transients in real-time. In collaboration with two legacy-style large survey projects (ThunderKAT and MeerTRAP) on MeerKAT (South Africa’s precursor to the Square Kilometre Array), MeerLICHT is the first fully dedicated telescope to follow another telescope in a different wavelength. Through linked-pointing, MeerLICHT and MeerKAT will provide simultaneous optical and radio data of the transient sky. This will provide invaluable information on emission at both wavelengths, including: the relation and evolution of emission from both wavelength windows, the discovery of optical counterparts of radio transients, the characterization of radio transients, and an early warning of radio transients using optical transients. This thesis contains the work on the development and implementation of the data processing pipeline for MeerLICHT. This data processing pipeline was developed for the automatic processing of data from MeerLICHT/BlackGEM for transient detection in real time.